COMPARISON OF POST OPERATIVE EPIDURAL ANALGESIA EFFECT USING CONTINUOUS 0.125% BUPIVACAINE WITH BOLUS 3 MG MORPHINE ON INSULIN LEVELS IN PATIENT UNDERGOING LOWER LIMB SURGERY - Yovalina R; Zulkifli Zulkifli; Zainal R; Erial Bahar (Majalah Kedokteran Sriwijaya, 2020)
The procedure for lower limb surgery is one of the major and long-standing operations. Surgical trauma stimulates the stress response of surgery. The surgical stress response will interfere with stress hormones including insulin. Insulin is an anabolic hormone that is important in the body and has a role in the process of wound healing. Previous studies have shown insulin levels to correlate with increased surgical stress and the type of anesthesia given. This study analyzed differences insulin levels in bupivacaine 0,125% with morphine 3 mg and to compare the analgesia effect of continuous bupivacaine 0,125% with 3 mg morphine epidural in postoperative lower extremity assessed from insulin levels. A retrospective cohort study taken from secondary data from previous studies and their medical records at RSUP Dr. Mohammad Hoesin Palembang. Statistical analysis used STATA 15th edition. Wilcoxon showed that there was a significant difference in 0,125% bupivacaine group on insulin leves after 12th hours postoperative (p<0.05). Man-Whitney showed that there was no significant difference between the 0,125% bupivacaine with 3 mg morphine on insulin levels postoperative lower extremity after 6th hours, 6th and 12th hours and after 12th hours (p>0.05). In this study, there was no significant difference between the 0,125% bupivacaine with 3 mg morphine on insulin levels